Pengaruh Kemampuan Kerja, Komitmen Kerja dan Motivasi Terhadap Kinerja Karyawan PTPN II SEI Semayang - Andini Putri Wardhani; Saimara A.M Sebayang (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
Ther rerserarch analysirs airms to derterrmirner ther irnfluerncer of work abirlirty, work commirtmernt and work motirvatiron on ermployerer perrformancer. Ther data analysirs terchnirquer userd irs an associratirver rerserarch merthod wirth ther herlp of ther SPSS verrsiron 19 program. Thirs rerserarch users multirpler lirnerar rergrerssiron analysirs. Ther sampler irn thirs study was 95 rerspondernts. Prirmary data collerctiron users a querstironnairrer. Ther rerserarch rersults show that work abirlirty has a posirtirver and sirgnirfircant erfferct on ther perrformancer of PTPN IrIr Serir Sermayang ermployerers. Work commirtmernt has a posirtirver and sirgnirfircant erfferct on ther perrformancer of PTPN IrIr Serir Sermayang ermployerers. Work motirvatiron doers do not haver a sirgnirfircant erfferct on ther perrformancer of PTPN IrIr Serir Sermayang ermployerers. Work abirlirty, work commirtmernt and work motirvatiron sirmultanerously haver a sirgnirfircant erfferct on ther perrformancer of PTPN IrIr Serir Sermayang ermployerers